Digital imaging systems for plain radiography - Lancca, Luis; Silva, Augusto (Springer, 2013)
This book addresses how exposure parameters influence the diagnostic quality in digital systems, what the current acceptable radiation doses are for useful diagnostic images, and at what level the dose could be reduced to maintain an accurate diagnosis